Tailoring epitaxial growth of low-dimensional magnetic structures by using surfactants - Camarero, Julio; de Miguel, J. J.; Graf, T.; Miranda, R.; Kuch, W.; Zharnikov, Michael; Dittschar, A.; Schneider, C. M.; Kirschner, J. (Surface science, 1998)
Ideal artificial materials such as magnetic thin films and superlattices are expected to possess unique properties owing to their reduced symmetry and dimensionality. In real systems, however, the actual behavior is extremely sensitive to the morphological features of the films and interfaces. {Co/Cu} heterostructures on Cu(111) are a prototypical example: their growth is complicated by several difficulties, such as the lack of interlayer diffusion or the appearance of stacking faults. We have been able to overcome these problems by using Pb as a surfactant during growth. In this way, ultrathin Co films and {Co/Cu} superlattices can be grown with custom-chosen properties: we can independently select to have either in-plane or out-of-plane magnetization, and ferro- or antiferro magnetic exchange coupling through the Cu spacer. The surfactant also prevents intermixing at the atomic steps, thus allowing us to grow one-dimensional structures (quantum wires).